2010
DOI: 10.1016/j.micinf.2010.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Acquired infection with Toxoplasma gondii in adult mice results in sensorimotor deficits but normal cognitive behavior despite widespread brain pathology

Abstract: Toxoplasma gondii is a ubiquitous intracellular parasite which chronically infects 30 to 50% of the human population. While acquired infection is primarily asymptomatic several studies have suggested that such infections may contribute to neurological and psychiatric symptoms. Previous studies in rodents have demonstated that T. gondii infection does not just kill its host, but alters the behavioral repertoire of an infected animal making it more likely that predation with occur completing the parasite life cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
78
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(106 citation statements)
references
References 49 publications
24
78
2
2
Order By: Relevance
“…In this regard the results of this study are in consistent with a previous study. Gulinello et al (2010) reported normal cognitive function, anxiety level, social behavior and the motivation to explore novel objects in mice after infection with T gondii.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard the results of this study are in consistent with a previous study. Gulinello et al (2010) reported normal cognitive function, anxiety level, social behavior and the motivation to explore novel objects in mice after infection with T gondii.…”
Section: Discussionmentioning
confidence: 99%
“…Parkinsonian symptoms have been reported in patients suffering from both toxoplasmosis and acquired immunodeficiency syndrome (AIDS), and anti-T. gondii medication reduced the observed symptoms (Carrazana et al, 1989;Murakami et al, 2000). In a mouse model system, T. gondii infection was found to generate sensorimotor deficits in animals without major brain damage or cognitive dysfunction (Gulinello et al, 2010). In addition to these links of T. gondii to schizophrenia, Parkinson's disease and OCD, T. gondii has been associated with Tourette's syndrome (P<0.07) (Krause et al, 2010) and a link with autism spectrum disorders has been speculated (Prandota, 2010).…”
Section: Toxoplasma and Neurological Disordersmentioning
confidence: 99%
“…In contrast, cognitive function, anxiety levels, social behavior, and motivation to explore new objects remain normal. The observed changes in behavior do not indicate severe brain damage and do not occur due to lesion in specific areas of the brain, which points out a subtle interaction of this parasite with its intermediate hosts and are suggestive of a greater predation due to this parasitic infection (GULINELLO et al, 2010).…”
mentioning
confidence: 71%